CO2 emission allowances and their interacion with economic and energy factors in the European Union - Botey Fullat , María; Arias Martín, Pedro; Alarcón, Silverio (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2021)
Analysis of emission allowances prices has important environmental and political connotations. This article aimed to identifying the possible variables that may influence their behaviour and studied their relationship with fundamental factors: energy (Brent petroleum, Gas, Coal) and economy (Industrial Production Index, Baltic Dry Index, Purchasing Managers Index). With the objective of analyzing possible mutual interactions, Multivariate VAR or Error Correction Models (VECM), were applied. The information analysed derived from different sources (World Bank, Sendeco2 and various financial websites). The results obtained showed, not only the influence of past prices on the emission allowances actual price, but also the interaction with energetic and economic variables. Highlights Estimation of time series interrelations through VAR models. There is relationship of the emission allowances price with their past values. The energy variables are factors important to also explain the behavior of the emission allowances price. The economic variables are hardly significant except for the Dry Baltic Index.